(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
In recent years, as a result of the implementation of complex measures to develop the textile and sewing-knitting industry in our country, to support the investment and export activities of industry enterprises, 45 percent of the cotton fiber and yarn produced in the republic is recycled. is being developed, and the annual export potential of the sector has exceeded 3.2 billion dollars. Developments on the basis of scientific research, such as the use of modern methods of obtaining cellulose and composite products based on it from the fiber waste of cotton gins, textile and other industrial factories, were analyzed.